Silicon nanostructuring by Ag ions implantation through nanosphere lithography mask - Modric-Sahbazovic, A.; Novakovic, Mirjana; Schmidt, E.; Gazdic, I.; Dokic, V.; Perusko, D.; Bibic, N.; Ronning, Carsten; Rakocevic, Z. (Optical Materials, 2019)
Nanosphere lithography is an effective technique for high throughput fabrication of well-ordered patterns on large areas. This study reports on nanostructuring of silicon samples by means of Ag ions implantation through self-organized polystyrene (PS) masks. The PS nanospheres with a diameter of ∼150 nm were self-assembled in a hexagonal array on top of Si(100) wafers, and then used as a mask for subsequent 60 keV silver ion implantation. Different fluences were applied up to 2 × 1016 ions/cm2 in order to create a distribution of different sizes and densities of buried metal nanoparticles. The surface morphology and the subsurface structures were studied by scanning electron microscopy and cross-sectional transmission electron microscopy, as a function of the mask deformation upon irradiation and the implantation parameters itself. We demonstrate that Ag is implanted into Si only through the mask openings, thus forming a regular array of amorphized regions over the wide area of silicon substrate. These fragments are of similar dimensions of the spheres with widths of about 190 nm and distributed over 60 nm in depth due to the given ion range. At the subsurface region of the implanted fragments, the synthesis of small sized and optically active Ag nanoparticles is clearly observed. The samples show a strong absorption peak in the long-wavelength region from 689 to 745 nm characteristic for surface plasmon resonance excitations, which could be fitted well using the Maxwell-Garnett`s theory.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Ag nanoparticles; Ion beam implantation; Nanostructuring; Polystyrene nanomask; Silicon; SPR peak